Engineering Aspergillus niger for galactaric acid production: elimination of galactaric acid catabolism by using RNA sequencing and CRISPR/Cas9. Issue 1 (December 2016) - Kuivanen, Joosu; Wang, Y.-M.; Richard, Peter
Abstract Background meso -Galactaric acid is a dicarboxylic acid that can be produced by the oxidation ofd -galacturonic acid, the main constituent of pectin. Mould strains can be engineered to perform this oxidation by expressing the bacterial enzyme uronate dehydrogenase. In addition, the endogenous pathway ford -galacturonic acid catabolism has to be inactivated. The filamentous fungusAspergillus niger would be a suitable strain for galactaric acid production since it is efficient in pectin hydrolysis, however, it is catabolizing the resulting galactaric acid via an unknown catabolic pathway. Results In this study, a transcriptomics approach was used to identify genes involved in galactaric acid catabolism. Several genes were deleted using CRISPR/Cas9 together with in vitro synthesized sgRNA. As a result, galactaric acid catabolism was disrupted. An engineeredA. niger strain combining the disrupted galactaric andd -galacturonic acid catabolism with an expression of a heterologous uronate dehydrogenase produced galactaric acid fromd -galacturonic acid. The resulting strain was also converting pectin-rich biomass to galactaric acid in a consolidated bioprocess. Conclusions In the present study, we demonstrated the use of CRISPR/Cas9 mediated gene deletion technology inA. niger in an metabolic engineering application. As a result, a strain for the efficient production of galactaric acid fromd -galacturonic acid was generated. The present study highlights the usefulness of CRISPR/Cas9 technology in the metabolic engineering of filamentous fungi.